Floral embroidery : create 10 beautiful modern embroidery projects inspired by nature - Sturmer, Teagan Olivia (Pen & Sword White Owl, an imprint of Pen & Sword Books Ltd, 2020)
"Floral Embroidery reawakens the age-old practice of embroidery, giving to it a new and modern twist. In this book, you will find 10 embroidery patterns that weave together stunning colors, ancient stitches, and florals picked from your grandmother's garden. From simple patterns, to more complex and intricate pieces, your creativity will grow and flourish. You will learn to stitch dusty pink roses, leaves and stems that will trail to the edges of your embroidery hoop, and the smallest details that will pull your hoop together and compose the most beautiful bouquet. Once you have completed the patterns, you will be given the tools to create your own original pieces and where to find the materials to do so." --